Cybersecurity and Custom Regulations as Trade Barriers in ASEAN e-Commerce: Case of Indonesian e-Commerce - Annisa Pratamasari (Global Strategis, 2020)
ASEAN countries show tremendous potential for e-commerce growth. Boasting its 650 million population and massive internet users, ASEAN proves to be a significant market for e-commerce and digital economy in general. Nonetheless, there are still some significant barriers in e-commerce trade, both traditional and non-traditional barriers of trade. Those barriers include a lack of harmonized regulations between the ASEAN Member States, high tariff duties on imported goods, and weak consumer protections (and overall cybersecurity) in the region. This study explores these barriers, which hinder ASEAN's goal to achieve more robust growth in the digital economy, particularly in terms of the legal framework (custom harmonization) and cybersecurity. In order to delve more deeply into these impediments of e-commerce trade, this article also attempts to present a study case of Indonesia's e-commerce as the most prominent and most promising player in ASEAN. Keywords: ASEAN, e-commerce, digital trade, digital economy  Negara-negara ASEAN menunjukkan potensi luar biasa bagi pertumbuhan e-commerce. Dengan jumlah penduduk 650 juta dan banyaknya pengguna internet, ASEAN terbukti menjadi pasar yang signifikan bagi e-commerce dan ekonomi digital secara umum. Meskipun demikian, masih terdapat beberapa hambatan signifikan dalam perdagangan e-commerce, baik hambatan perdagangan tradisional maupun non-tradisional. Hambatan-hambatan itu termasuk kurangnya regulasi yang harmonis antara negara-negara anggota ASEAN, bea masuk yang tinggi untuk barang-barang impor, dan lemahnya perlindungan konsumen (serta keamanan cyber secara keseluruhan) di dalam kawasan. Penelitian ini mengeksplorasi hambatan-hambatan yang menghambat tujuan ASEAN untuk mencapai pertumbuhan yang lebih kuat dalam ekonomi digital, terutama dalam hal kerangka hukum (harmonisasi aturan) dan keamanan cyber. Untuk menggali lebih dalam hambatan-hambatan perdagangan e-commerce ini, tulisan ini juga mencoba untuk menyajikan studi kasus e-commerce Indonesia sebagai pemain terbesar dan paling menjanjikan di ASEAN. Kata-kata kunci: ASEAN, e-commerce, perdagangan digital, ekonomi digital